Analysis methods of modeling the junction bezrebrystoyi bezkapitelnoyi concrete slabs and columns - Барабаш, М.С.; Омельченко, Е.В. (Proceedings of National Aviation University (archive), 2009)
Analysis of different ways desighn of the junction of girdless plate) and column without chapiter in program complexes LIRA, MONOMAH.